2022
DOI: 10.5552/crojfe.2022.1541
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Data Efficiency Evaluation of Forest Companies

Abstract: The forestry sector is facing critical challenges due to climate change. Decision-making support based on efficiency evaluation using non-parametric methods could provide important information for both forest managers and policymakers. However, such advanced technical analysis is scarce in forestry science. When applied, its application has been primarily based on aggregated, macro-level data, and efficiency was analysed for the forestry sector as a whole. There is a lack of studies from the company-level pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The sources of data include the Cathay Pacific database, Prospective Economy Network, and the annual reports of each company. To ensure that the sample is representative, this study combines existing research results and selects total assets (Stankov a et al, 2022;Yang et al, 2016;Li et al, 2023), operating costs and number of employees as input indicators of a company's operating efficiency. Meanwhile, operating income, net profit and return on net assets are selected as output indicators of operating efficiency to comprehensively reflect the company's main business operation, profitability and investor profitability.…”
Section: Data Sources and Variable Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The sources of data include the Cathay Pacific database, Prospective Economy Network, and the annual reports of each company. To ensure that the sample is representative, this study combines existing research results and selects total assets (Stankov a et al, 2022;Yang et al, 2016;Li et al, 2023), operating costs and number of employees as input indicators of a company's operating efficiency. Meanwhile, operating income, net profit and return on net assets are selected as output indicators of operating efficiency to comprehensively reflect the company's main business operation, profitability and investor profitability.…”
Section: Data Sources and Variable Selectionmentioning
confidence: 99%
“…The sources of data include the Cathay Pacific database, Prospective Economy Network, and the annual reports of each company. To ensure that the sample is representative, this study combines existing research results and selects total assets (Stanková et al. , 2022; Yang et al.…”
Section: Evaluation Of Operating Efficiency Of Forest Product Process...mentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the analysis of four Central European countries (Czech Republic, Germany, Hungary, Slovakia) in the period between 2009 and 2016, Staňková et al (2022), using DEA and the stochastic frontier analysis method, found that there are differences in efficiency depending on the size of enterprises. State-owned enterprises, which are among larger enterprises, have lower efficiency because they try to promote other (government) objectives, such as employment.…”
Section: Introductionmentioning
confidence: 99%